Stellilabium kukwae (Telipogoneae, Orchidaceae), a new species from Bolivia - Szlachetko, Dariusz; Mytnik-Ejsmont, Joanna (Biodiversity: Research and Conservation, 2011)
A new species from Bolivia of the genus Stellilabium Salisb. (Telipogonae, Orchidaceae), S. kukwae Szlach. & Mytnik, is described and illustrated. It is morphologically most similar to S. pampatamboense Dodson & R.Vásquez, but it is distinct in having densely, entirely ciliate petals, scarcely ciliate lip laminae, and furculate hairs covering the gynostemium.